PENGARUH LATIHAN AKUT LARI 30 M TERHADAP PENINGKATAN FREKUENSI DENYUT NADI DAN PERNAFASAN PADA ATLET BOLA BASKET PUTRI SMPN 17 PEKANBARU - Randhi Sapta Yuana; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted by the Basketball Team of Putri SMPN 17 Pekanbaru, bolabasket education curriculum is one of extracurricular activities that very excluded by the students. Extracurricular activities this bolabasket has been running well but still a lot also often happens when playing games. Obstacles include: often making the ball during an assault to the opponent's area, generally the frequency of the pulse and breathing, then the posture of the player who is under the players of the opponent. The purpose of this study is to know: